Influence of Employee Involvement in Total Productive Maintenance Practices on Job Characteristics: The Malaysian Scenario - Aizzat Mohd. Nasurdin; Muhamad Jantan; Wong Wai Peng; T. Ramayah (Gadjah Mada International Journal of Business, 2005)
The main goal of this study is to examine whether the extent of involvement in Total Productive Maintenance (TPM) practices has a positive effect on job characteristics. Data was gathered from a sample of 184 respondents derived from manufacturing companies in Malaysia. Results from the regression analyses revealed that the extent of employee’s involvement in TPM practices is positively related to the five core job dimensions (skill variety, task identity, task significance, autonomy, and feedback). Theoretical and managerial implications of the findings are discussed.